2018
DOI: 10.3390/pharmaceutics10030133
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and Brain Distribution of the Active Components of DA-9805, Saikosaponin A, Paeonol and Imperatorin in Rats

Abstract: DA-9805 is a botanical anti-Parkinson’s drug candidate formulated from ethanol extracts of the root of Bupleurum falcatum, the root cortex of Paeonia suffruticosa, and the root of Angelica dahurica. The pharmacokinetics (PKs) and brain distribution of active/representative ingredients of DA-9805, Saikosaponin a (SSa; 1.1–4.6 mg/kg), Paeonol (PA; 14.8–59.2 mg/kg), and Imperatorin (IMP; 1.4–11.5 mg/kg) were evaluated following the intravenous or oral administration of each pure component and the equivalent dose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Our present study first found that SSa could promote Statistical comparisons were conducted using one-way analysis of variance (ANOVA) followed by protected least significant difference (PLSD) tests. Data represented as mean ± SEM (n = 6), *p < 0.05, **p < 0.01, n.s., no significant difference between two groups rat is 17.5 min (Kwon et al, 2018). Considering that SSa is watersoluble, which means that SSa is comparably hard to penetrate the blood-brain barrier, and the LH is located deep in the brain, the extended time to taking effect might be partly contributed to by the time spent on drug transmission to the target.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Our present study first found that SSa could promote Statistical comparisons were conducted using one-way analysis of variance (ANOVA) followed by protected least significant difference (PLSD) tests. Data represented as mean ± SEM (n = 6), *p < 0.05, **p < 0.01, n.s., no significant difference between two groups rat is 17.5 min (Kwon et al, 2018). Considering that SSa is watersoluble, which means that SSa is comparably hard to penetrate the blood-brain barrier, and the LH is located deep in the brain, the extended time to taking effect might be partly contributed to by the time spent on drug transmission to the target.…”
Section: Discussionmentioning
confidence: 93%
“…In our present study, it is surprising to find that SSa does not have any effect during the first hour after injection. Based on previous studies, the time taken to reach the maximum concentration (T max ) of 2.3 mg/kg SSa after oral administration in the Sprague‐Dawley rat is 17.5 min (Kwon et al, 2018). Considering that SSa is water‐soluble, which means that SSa is comparably hard to penetrate the blood–brain barrier, and the LH is located deep in the brain, the extended time to taking effect might be partly contributed to by the time spent on drug transmission to the target.…”
Section: Discussionmentioning
confidence: 99%
“…The tubes were incubated for 60 min in a water bath at 37 • C. Phenacetin (50 µM, 300 µL) dissolved in ice-cold HPLC-grade acetonitrile was added to each incubation tube for reaction termination. Protein separation was obtained in each incubation tube after centrifuging at 13,000× g for 5 min using a micro centrifuge [16]. Finally, 500 µL of supernatant was collected from each tube and mixed with 300 µL of mobile phase in HPLC vials.…”
Section: Potential Assessment Of Ugt2b17 Assay Inhibition By Salicylic Acid In Vitromentioning
confidence: 99%
“…The metabolic type of PAE in the liver was mainly Phase I metabolism, and the main metabolites were 2, 4-dihydroxyacetophenone and four kinds of oxidative metabolites. 26 Reduced nicotinamide adenine dinucleotide phosphate (NADPH) is an indispensable auxiliary factor in the biotransformation of many compounds, which is involved in the reaction of CYP450 enzymes, FMOs enzymes and other oxidases in liver microsomes. 27 The metabolic mechanisms of PAE in different simulated biological samples are shown in Table 2.…”
Section: Stability Of Pae In Simulated Biological Samplesmentioning
confidence: 99%